2018
DOI: 10.1039/c7cy02488f
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic studies on the N-alkylation of amines with alcohols catalysed by iridium(i) complexes with functionalised N-heterocyclic carbene ligands

Abstract: Experimental and theoretical studies give support for an iridium-catalyzed C–N bond formation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 96 publications
(36 reference statements)
1
18
0
Order By: Relevance
“…In accordance with the previous reports, [ 18,27,65,66 ] a plausible mechanism for the N‐ alkylation of amines with alcohols is proposed as shown in Scheme 3. The reaction initiated by the formation of I , which is formed via the elimination of HCl.…”
Section: Resultssupporting
confidence: 89%
“…In accordance with the previous reports, [ 18,27,65,66 ] a plausible mechanism for the N‐ alkylation of amines with alcohols is proposed as shown in Scheme 3. The reaction initiated by the formation of I , which is formed via the elimination of HCl.…”
Section: Resultssupporting
confidence: 89%
“…[ 53–55 ] Other authors have reported that this process is more favored by water [ 56 ] or alcohols [ 57 ] than by some metallic species. In contrast, other theoretical [ 21,58,59 ] and experimental [ 21 ] studies indicate that the condensation step takes place in the coordination sphere of the catalyst. In order to delve this question, we monitored by 1 H NMR the reaction of benzaldehyde and p ‐toluidine in a molar ratio 2:1 in TFE media in the absence of catalyst, and we found that this reaction was completed at room temperature in 5 min (see Figure S11).…”
Section: Resultsmentioning
confidence: 88%
“…The condensation reaction is promoted by acidic species and except in a few cases does not involve the participation of the metallic catalyst. [ 21 ] Nevertheless, the BH methodology requires the participation of metal complexes able to promote processes I and III. [ 22,23 ] During the last years, several groups have contributed to the development of this strategy with metal complexes, mainly of Ir, including highly active iridacyles, [ 13 ] Rh and Ru, [ 21,24–28 ] as well as other transition metals [ 29,30 ] and heterogeneous systems, [ 31–33 ] Catalysts active even in water and ionic liquids [ 34 ] or in solvent‐free conditions [ 35 ] have been reported, but the majority of catalysts are used in organic solvent media.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…N‐alkylation of aniline with benzyl alcohol was, initially, chosen as a model reaction (Figure 7), to examine the catalytic activity of Ir−PPy NPs.The results of the tests carried out by using the catalyst in the presence of different bases, and with bases or PPy alone, are reported for comparison in Table 1 and Table 2, Figures 8 and 10 and Figures S1–S11. The data show that the kinetic of imine formation is faster than that of hydrogenation to the secondary amine [13d] . In particular, in Table 1 and Table 2 the results of the tests performed with benzyl alcohol (1 mmol), aniline (1 mmol), catalyst (25 mg at 2 wt.% Ir), base (2 mmol), toluene (5 mL), at 100 °C and under N 2 were shown after 12 and 24 hours, respectively.…”
Section: Resultsmentioning
confidence: 94%